2014
DOI: 10.1371/journal.pone.0092947
|View full text |Cite
|
Sign up to set email alerts
|

The Chromatin “Landscape” of a Murine Adult β-Globin Gene Is Unaffected by Deletion of Either the Gene Promoter or a Downstream Enhancer

Abstract: In mammals, the complex tissue- and developmental-specific expression of genes within the β-globin cluster is known to be subject to control by the gene promoters, by a locus control region (LCR) located upstream of the cluster, and by sequence elements located across the intergenic regions. Despite extensive investigation, however, the complement of sequences that is required for normal regulation of chromatin structure and gene expression within the cluster is not fully defined. To further elucidate regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…2h). We find that, in concordance with detailed genetic gene competition studies at this locus [18][19][20] , partnering at the enhancer hub is allowed between developmentally synchronized genes, but not between genes active at different stages of development. The uncovered higher-order conformational features therefore provide a topological framework that helps interpreting the genetic observations.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…2h). We find that, in concordance with detailed genetic gene competition studies at this locus [18][19][20] , partnering at the enhancer hub is allowed between developmentally synchronized genes, but not between genes active at different stages of development. The uncovered higher-order conformational features therefore provide a topological framework that helps interpreting the genetic observations.…”
supporting
confidence: 81%
“…Genetic studies in mice further demonstrated that the two developmentally distinct sets of genes compete for activation between sets, but not among members of each set, and that the four enhancer elements of the SE can compensate to a high degree for each other's activity 19,20 . We performed MC-4C experiments in both fetal liver, where the adult genes are highly expressed and in fetal brain where the b-globin locus is transcriptionally silent.…”
mentioning
confidence: 99%
“…These results strongly suggest that LCR/β min looping depends on KLF1. They also are supportive of a β maj /β min competition model, although this issue is unresolved ( 45 , 46 ).…”
Section: Resultsmentioning
confidence: 91%
“…It is interesting to compare our data with other recently published examples of developmental enhancer deletion. A study of single conserved limb enhancers showed that 90% of these had no impact on cognate gene expression (21), as well as highly conserved ß-globin enhancers (22). Computational analyses have predicted that most (96%) of enhancers within the genome are tolerant to LoF mutations, and that many essential genes will have a degree of enhancer redundancy (23).…”
Section: Discussionmentioning
confidence: 99%
“…Computational analyses have predicted that most (96%) of enhancers within the genome are tolerant to LoF mutations, and that many essential genes will have a degree of enhancer redundancy (23). In the vast majority of examples, deletion of a single conserved enhancer element has no impact on cognate gene expression (21, 22). The Nestin enhancer therefore appears to be unusual in having such a profound impact on Nes expression during early embryonic development.…”
Section: Discussionmentioning
confidence: 99%